2015
DOI: 10.3329/bjp.v10i1.20639
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> phytochemical and antimicrobial screening of <i>Thymus linearis</i>

Abstract: Various solvent extracts from the whole plant of Thymus linearis were screened for their phytochemical and antimicrobial potentials. Preliminary phytochemi-cal screening of plant extracts showed the existence of terpenoids, flavonoids, tannins, alkaloids, glycosides and reducing sugars. Fourier transform infrared spectroscopy studies were carried out on various phytochemicals extracted from the exhibited T. linearis which resulted in the presence of different compounds like amides, aldehydes, carboxylic acid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Pant and Samant (2010) reported that whole plant of Thymus linearis is given to women during labor and postnatal period. The plant is reported to possess some important secondary metabolites including terpenoids, flavonoids, tannins, alkaloids and glycosides (Naz et al 2015) and has anti-inflammatory, antipyretic, hepatoprotective, and antibacterial activities (Ahmad et al 2014;Naz et al 2015). In the current study root decoction of Geranium wallichianum is used to relieve labor pain.…”
Section: %mentioning
confidence: 82%
“…Pant and Samant (2010) reported that whole plant of Thymus linearis is given to women during labor and postnatal period. The plant is reported to possess some important secondary metabolites including terpenoids, flavonoids, tannins, alkaloids and glycosides (Naz et al 2015) and has anti-inflammatory, antipyretic, hepatoprotective, and antibacterial activities (Ahmad et al 2014;Naz et al 2015). In the current study root decoction of Geranium wallichianum is used to relieve labor pain.…”
Section: %mentioning
confidence: 82%
“…Asparagus racemosus (Asparagaceae) is commonly called as 'Kurilo'; traditionally used to cure stomach problems and skin diseases [24] and have antihepatotoxic, antineoplastic, antiprotozoal, adaptogenic, antiulcer, antioxidant, antilithiatic, antidepressant, anti-inflammatory, and cytotoxicity activities [25]. Thymus linearis (Lamiaceae) is commonly called as 'Ghodamarcha'; traditionally used to cure stomach problems, cough, cold, and eye infection [26] and have antihypertensive [27], anti-inflammatory, antipyretic [28], hepatoprotective [29], antioxidant, anticholinergic [30], and antimicrobial [31] activities. Pleurospermum benthamii (Apiaceae) is commonly called as 'Gandhaina' and used to cure Diarrhea, dysentery, constipation, gastritis, cough, cold, headache, and indigestion [2].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical analysis of crude extract of plant showed presence of flavonoids, sterols, steroids and triterpenoids. These essential oils have already been reported to have analgesic, anti-inflammatory and antipyretic activities by inhibition of COX enzyme by a mechanism same like non-steroidal anti-inflammatory drugs [18,19]. Therefore, the analgesic, antiinflammatory and antipyretic activities of Thymus linearis may be due to these compounds.…”
Section: Discussionmentioning
confidence: 98%